Analisis Current Ratio dan Debt To Asset Ratio (DAR) Terhadap Return On Investment Pada PT. Mayora Indah, Tbk Periode 2016-2020 - Asrul; Nimas Ayu Arumbinang (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
This study aims to analyze the effect of Current Ratio and Debt Asset to Ratio on Return on Investment simultaneously and partially. The object of research is a food company listed on the Indonesia Stock Exchange. The data analysis is the financial statements (Balance Sheet and Income Statement) for 2016-2020, using ratio analysis and multiple regression techniques. The results obtained from multiple linear regression analysis Y = 0.037 + 0.051X1 - 0.003 X2 Simultaneously have an effect on Return on Investment. In the analysis of the coefficient of determination obtained R2 y = 0.325. This means that the Current Ratio (X1) and Debt Asset to Ratio (X2) variables have a weak and positive relationship with the Return on Investment (y) variable. analysis of the coefficient of determination as follows: Kd = R2 x 100% = 32.5%, meaning that changes in the value of the Return on Investment variable can be explained by the Current Ratio and Debt Asset to Ratio. While the remaining 67.5% is influenced by other factors. The results of the t-test of the Current Ratio (X1) variable on Return on Investment show Ttable > Tcount 1.447 < 2,100, with a significance level less than 0.05. So, it can be concluded that the Current Ratio does not have a significant effect on the return on investment variable. The variable Debt Asset to Ratio (X2) to Return on Investment (Y) shows T table > T count 0.122 > 2.100, with a significance level of less than 0.05. Resulting in a conclusion that the Debt Asset to Ratio has no effect on Return on Investment. The results of the comprehensive test (Test f) through SPSS Version 22 can be seen from the results of Fcount <Ftable 4097> 3.55 with a significance level of 0.035> 0.05. Then the independent variables Current Ratio and Debt Asset to Ratio (independent) together have a positive and significant effect on the variable Return on Investment (dependent) PT. Mayora Indah Tbk.